Beginning Java ME Platform - Rischpater, Ray (Apress, 2012)
When I set out to write this book, I was often surprised by the comments I received from friends and colleagues. Many asked me if some other platform, such as Android or the iPhone, would render Java Platform, Micro Edition (Java ME) obsolete (and nonexistent, some posited) by the time the book is published. Still others pointed to the growing convergence between different lines of Java as rendering the need for separate information about Java ME obsolete. And a few remarked scathingly that the market for Java books was saturated, so investing the time to write another was an exercise in futility. You, too, may ask these questions as you decide whether or not to read this book. Perhaps you’re interested in Java ME as a specific platform on which to deploy an existing product, or perhaps you’re just curious as to whether you should include Java ME skills in your professional portfolio